2009
DOI: 10.1590/s1519-69842009000200019
|View full text |Cite
|
Sign up to set email alerts
|

Steviol effect, a glycoside of Stevia rebaudiana, on glucose clearances in rats

Abstract: Stevia rebaudiana, a South American plant normally used as a natural herbal sweetener, has been suggested as exerting beneficial effects on human health, including as an antihypertensive and antihyperglycemic. The present experiment was undertaken to evaluate the renal excretion of steviol, the aglycone of several natural products extracted from the leaves of S. rebaudiana, and to clarify the actual participation of this compound on the renal excretion of glucose in rats, which has been previously suggested as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
0
9
0
4
Order By: Relevance
“…Stevioside and steviol induce diuresis and natriuresis, without a significant change in glomerular filtration rate or renal plasma flow [81]. It was found that in the diabetic rats fed with Stevia on renal function observed remarkable reduction in the glomerular filtration rate (GFR) and renal plasma flow (RPF).…”
Section: Renal Protectivementioning
confidence: 99%
“…Stevioside and steviol induce diuresis and natriuresis, without a significant change in glomerular filtration rate or renal plasma flow [81]. It was found that in the diabetic rats fed with Stevia on renal function observed remarkable reduction in the glomerular filtration rate (GFR) and renal plasma flow (RPF).…”
Section: Renal Protectivementioning
confidence: 99%
“…It has been described that the hypotensor effect of stevioside is due to the inhibition of the influence of calcium from the extracelular fluid 49 . Plus, it has been shown that stevioside and steviol induce diuresis and natriuresis, without a significant change in glomerular filtration rate or renal plasma flow 50 . All this.…”
Section: Propertiesmentioning
confidence: 99%
“…The evidence suggests that stevioside improves secretion and sensitivity to insulin 18 . Besides, it generates the concomitant suppression of glucagon's secretion 18 and the decline in the renal tubular reabsorption of glucose 50 .…”
Section: Propertiesmentioning
confidence: 99%
“…Jest białym, krystalicznym, bezwonnym proszkiem wyekstrahowanym z liści stewii, stanowiącym 6 -18 % ich świe-żej masy [9,13,18]. Zawiera trzy cząsteczki glukozy oraz stewiol [21]. Jest odpowiedzialny za gorzkawy posmak stewii.…”
Section: Substancje Biologicznie Aktywneunclassified